Traumatismo encefálico con fractura de cráneo. Tratamiento médico y quirúrgico. Reporte de un caso (2002)
ABSTRACT: A six-year-old female Miniature Pinscher arrived to the Veterinary Teaching Clinic of the University of Antioquia, in a state of delirium with tonic clonic convulsions after being attacked by another dog. Physical examination revealed a skull fracture, which was confirmed by radiographs. Initial assessment was focused to reduce the intracraneal pressure, but no neurological improvement was achieved, so surgery was performed. This procedure allowed the total remission of the neurological symptoms. Up to date no sequels of the incident have appeared.